ans this question correctly plz. help fast
Attachments:
![](https://hi-static.z-dn.net/files/dbc/17eb849f3729bc21d66343b213d0b5fc.jpg)
Answers
Answered by
1
Hey dude....m=1
Because...the base are same... So we add the power....
M+1+5=7
M+6=7
M=1
Hope it helps..
Because...the base are same... So we add the power....
M+1+5=7
M+6=7
M=1
Hope it helps..
sachinkumar12431:
here is your answer
Answered by
4
(-3)^(m+1)×(-3)^5=(-3)^7
=>(-3)^(m+1+5)=(-3)^7
=>(m+6)=7
=>m=7-6=1
HOPE IT WILL HELP YOU
plz Mark me as a brainliest
=>(-3)^(m+1+5)=(-3)^7
=>(m+6)=7
=>m=7-6=1
HOPE IT WILL HELP YOU
plz Mark me as a brainliest
Similar questions